Identifikasi Karakteristik Agronomi Dan Morfologi Beberapa Varietas Padi Lokal Di Lahan Rawa Lebak - Jumakir, Jumakir; Aswandi, Aswandi; Aryunis, Aryunis (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2024)
Characterization is a process  observation of  knowing the character a plant. The aim of the study was to identify agronomic and morphological characteristics as well as the kinship of several local rice varieties in the lebak swampland. This research was carried out in Mudung Laut Village, Pelayangan District, Jambi Province with a middle lebak swampland agroecosystem from July to December 2022. The design used was Randomized Group with three replicates, with 14 local rice and two superior rice varieties, are Pandan Wangi Kuning, Mawar, Putih, Tinggi, Ketan Hitam, Napi, Serendah Layap, Bujang Berinai, Kuning, Janu, Melati, Sentani, Bendera, Pandan Wangi, Padi Merah dan Inpara 3.   Quantitative data using analysis of variance, if there are differences continued with the Scott Knott test at the level of α = 5%. Quantitative data to determine the kinship of rice varieties was carried out by cluster analysis.  The research results, it was found that there was a diversity of morphological characters in various local swamp rice varieties and significantly different in all variables which could be caused by genetic and environmental factors biotic and abiotic. Analysis of kinship  rice varieties in Swamp Lebak has a similarity coefficient value ranging from 0.71 to 1.00.